1999
DOI: 10.1177/0011000099273007
|View full text |Cite
|
Sign up to set email alerts
|

Neuropsychological Training in APA-Accredited Counseling Psychology Programs

Abstract: The availability of neuropsychological training in American Psychological Association-accredited counseling psychology programs was examined. A survey response rate of 53% (33/62) was obtained from program training directors. Only 42% (14/33) reported the availability of a neuropsychology course at their universities. Results indicated that counseling psychology students are interested in neuropsychological theory and assessment but may have difficulty finding training within their academic programs and instit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0

Year Published

2001
2001
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 14 publications
1
11
0
Order By: Relevance
“…Perhaps the only new development was the high endorsement of "generic neuropsychological tests" (ranked fourth), which is consistent with a recent study that found that neuropsychological training was making large gains in APA-accredited counseling psychology programs (see Ryan & Lopez, 1999). What we found most startling about these findings is that these top-ranked instruments are the very tests that have been identified by practitioners as most noted for decreased use in contemporary clinical practice, largely due to managed care constraints (Piotrowski et al, 1998).…”
Section: Discussionsupporting
confidence: 76%
“…Perhaps the only new development was the high endorsement of "generic neuropsychological tests" (ranked fourth), which is consistent with a recent study that found that neuropsychological training was making large gains in APA-accredited counseling psychology programs (see Ryan & Lopez, 1999). What we found most startling about these findings is that these top-ranked instruments are the very tests that have been identified by practitioners as most noted for decreased use in contemporary clinical practice, largely due to managed care constraints (Piotrowski et al, 1998).…”
Section: Discussionsupporting
confidence: 76%
“…This set of articles greatly influenced the third theme, Integrating Neuropsychology. There were also two other articles published later in the 1990s that focused on this integration (Lopez, Ryan, & Sumerall, 1998;Ryan, Lopez, & Lichtenberg, 1999). The second distinct period consisted of six articles that were published in 2014, all in a special section of the Journal of Counseling Psychology, focusing on the integration of counseling psychology and neuroscience (Coutinho et al, 2014;Fine & Sung, 2014;Gonçalves & Perrone-McGovern, 2014;Sampaio & Lifter, 2014;Simon-Dack & Marmarosh, 2014;Wright & Díaz, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…The first group of literature from the USA was related to integrating neuropsychology into counselling psychology (Agresti, 1992;Corazzini, 1992;Kemp, 1992;Larson, 1992;Larson & Agresti, 1992;Malec, 1992;Paulsen, 1992;Woody, 1992;Lopez, Ryan, & Sumerall, 1998;Ryan, et al, 1999). As discussed in section 1.2, I see a distinction between neuropsychology and neuroscience; however I still viewed this literature as relevant to the present topic as there is without doubt a huge neuroscience aspect in the field of neuropsychology.…”
Section: Integration Of Neuropsychology and Counselling Psychologymentioning
confidence: 98%
“…Increased neuropsychological knowledge could also support intervention planning with neurological and learning difficulty populations (Kemp, 1992). It was suggested that not only is neuropsychological work on the increase for psychologists, but that counselling psychologists want to get on board with it and have a lot to offer (Agresti, 1992;Corazzini, 1992;Kemp, 1992;Larson, 1992;Larson & Agresti, 1992;Malec, 1992;Paulsen, 1992;Woody, 1992;Ryan, et al, 1999), not just in practice but in research as well (Kemp, 1992, Paulsen, 1992Lopez, et al, 1998).…”
Section: Integration Of Neuropsychology and Counselling Psychologymentioning
confidence: 99%